516. Delivery Mode and Intrapartum Antibiotics Affect the Gut Mycobiome in Newborn Infants and Young Children. (15th December 2022) - Turunen, Jenni; Paalanne, Niko; Reunanen, Justus; Tapiainen, Terhi; Tejesvi, Mysore V
Abstract: Background: The gut mycobiome may have important effects on health. Yet, there is limited data on the mycobiome. Previously, we have shown that antibiotic exposure at birth markedly alters the gut bacteriome in children. As fungi and bacteria may have important interactions in the gut microbiome, we hypothesized that perinatal antibiotics may influence the composition of the gut mycobiome. Methods: For the study, 434 fecal samples were collected at birth, 6 months, and 18 months of age. We extracted DNA from samples using DNeasy PowerSoil Pro kit. We sequenced the ITS2 gene and analyzed the results using QIIME2. The taxonomy was assigned using UNITE database. Results: At birth, newborn infants had a low-biomass gut mycobiome, which developed over time until the age of 18 months. At the genus level, there was a transition from Candida to Trichosporon and Saccharomyces at 6 and 18 months respectively. Unidentified fungi were found in greater numbers in 18-month stool samples than in earlier samples. Alpha and beta diversity analyses showed statistically significant differences depending on the age of infants. Both delivery mode and intrapartum antibiotics were associated with significant differences in the gut mycobiome composition. Infants born vaginally had mycobiome with abundant Candida at birth and their mycobiome progressed towards composition dominated by Trichosporon and Saccharomyces . Samples from infants born via C-section had more Malassezia, Hyalotiella and Saccharomyces. Vaginally delivered infants exposed to antibiotics at birth had more Candida sp. in the gut mycobiome than those unexposed to antibiotics. By 18 months of age, half of the fungi in no intrapartum antibiotic group were unidentified fungi, but more than half of the fungi in the intrapartum antibiotic group were of genus Trichosporon. Figure 1. Taxonomic figures of each sample type. Taxa have been drawn from phylum (innermost level) to species (outermost level). Figure 2. Taxonomic figures of each sample type are based on the delivery mode. Taxa have been drawn from phylum (innermost level) to species (outermost level). Figure 3. Taxonomic figures of each vaginal delivery sample are based on the usage of intrapartum antibiotics. Taxa have been drawn from phylum (innermost level) to species (outermost level). Conclusion: In this prospective cohort study, the gut mycobiome composition of newborn infants and young children was markedly influenced both by delivery mode and exposure to antibiotics at birth. The effects were observed from birth until 18 months of age. Disclosures: All Authors : No reported disclosures.